Analysis of the Economic Potential of Porang Plants and Porang Content Creator Through the YouTube Platform - Maemunah Nurmaya Sari; Andri Waskito; Saripah Saripah (Sosio e-Kons, 2022)
The Porang plant has recently gained popularity due to its high selling value and has become a superior export commodity that is in demand by many countries. The data shows that there is a significant increase in searches with the keyword "Porang". This research with a qualitative approach using website-based data examines several content creators about porang. Research reveals that YouTube is proving to be useful as a communication or promotion tool.This plant, which has the Latin name Amorphophallus muelleri, has significant economic benefits as a mainstay commodity that is traded across countries, efficient porang plant management will generate revenues that far exceed the costs invested. From the search results on the YouTube website, it is known that the number of content creators with the main topic of porang is relatively small. YouTube channels with headlines about porang have an average YouTube channel subscriber of under 200,000 subscribers. Five of the 6 YouTube channels that cover the main topic of porang use the word “Porang” in the name of the YouTube channel. In this study, strategies are presented to maximize YouTube channels. The channel with the most subscribers has prove implemented steps to maximize the YouTube channel.